(untitled) - Karlen, Mark (Hoboken, 2004)
The author’s step-by-step space planning approach demonstrates how to use matrices and diagrams to fully visualize the space analysis process, including how to apply bubble diagrams and block plans for establishing a workable spatial organization. With a focus on existing structures, this comprehensive book presents material in a realistic context to create a hands-on guide that helps develop applicable skills and provides accessible information for solving day-to-day issues in the real world.
Keywords: Interior architecture,Space (Architecture)